The Influence of Stock Liquidity, Debt Maturity and Institutional Ownership on The Stock Price Crash Risk of Companies Listed on The LQ45 Index from 2019-2023 - Aprilia, Fika; Murdijaningsih, Tjahjani; Danuta, Khrisnoe Sukma (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to analyze the effect of stock liquidity, debt maturity, and institutional ownership on the stock price crash risk of companies listed on the LQ45 index from 2019 to 2023. The population of this study consists of companies listed on the LQ45 index for five consecutive years, selected using a purposive sampling technique, resulting in a sample of 23 companies. This study uses secondary data in the form of financial reports obtained from the Indonesia Stock Exchange and other sources, namely Yahoo Finance. The data were analyzed using a panel regression analysis technique. The results of this study indicate that debt maturity has a positive and significant effect, while stock liquidity and institutional ownership have no significant effect on the stock price crash risk of companies listed on the LQ45 index from 2019 to 2023.